Extraction of Enzymes from Spent Compost of Pleurotus Sajor-Caju and its Potential Use for Decolourisation of Synthetic Dyes - Avncesh U, Singh; S, Vikineswary; Abdullah, Noorlidah (Malaysian Journal of Science, 2002)
Extraction of enzymes from 5-month old spent mushroom compost of P. sajor-caju by homogenization for eight min at 8000 rpm using tap water at pH 4 had an advantage over the use of an incubator shaker. Both lignin peroxidase (103.42 Ug^-1) and 3-glucosidase (132.07 Ug^-1) were present at high levels and there was a further 5.5 fold increase of lignin peroxidase and 3.7 fold increase of β-glucosidase when concentrated. Other enzymes present in the spent mushroom compost at lower levels were laccase (0.15 Ug^-1), carboxymethyl cellulase (1.71 Ug^-1) and xylanase (6.62 Ug^-1). This mixture of concentrated enzymes which mainly consists of lignin peroxidase and β - glucosidase showed good potentials to decolourize crystal violet, trypan blue and amido black. The percentage decolourisation of remazol brilliant blue R was only significant at high concentration of lignin peroxidase (25 U) while no decolourisation was observed for methyl green. The study showed significant depolarization of all the dyes in the presence of 1 mM veratryl alcohol.